Perilaku Manajemen Laba Pada Masa Pandemi: Studi Pada Industri Perbankan - Muhamad Zauqi Rachman; Khomsiyah Khomsiyah (Politeknik Ganesha Medan, 2022)
The purpose of this study is to evaluate how corporate social responsibility and firm size moderated by good corporate governance affect earnings management. The financial statements of companies listed on the IDX for 2019–2021 are the data used in this analysis. The Indonesia Stock Exchange (IDX) website provides information for this research (www.idx.co.id). There are 45 companies and 135 samples registered in 2019 to 2021. The sample in this study is the banking industry sector. There are 40 companies that meet the criteria. This study aims to determine whether corporate social responsibility and company size affect earnings management. As a result, there is no effect of corporate social responsibility moderated by good corporate governance on earnings management. This study shows the results that corporate social responsibility, profitability, leverage, and audit firm have no effect on earnings management. Likewise, corporate governance as moderated variable has no effect on earnings management, but managerial ownership and the board of commissioners as proxies of corporate governance show that they are able to weaken the influence of corporate social responsibility and company size on earnings management, while firm size moderated by good corporate governance has a positive effect on earnings management to reduce the company’s practice in doing earnings management.